1998
DOI: 10.1159/000053062
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Defects in the Control of Growth Hormone Secretion

Abstract: Since growth hormone deficiency (GHD) causes short stature and metabolic derangements, the processes which control its release are important physiologically. These processes can be illuminated by an understanding of genetically determined GHD. In 2 Indian Moslem cousins from a consanguineous family, GHD resistant to growth hormone releasing hormone (GHRH) stimulation was found. No mutations were found in the growth hormone gene (GH1) (J. Phillips). The receptor for GHRH (GHRHR), implicated in the dwarfism of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This observation is most likely due to random sampling, given the low expected values for the Val/Val genotype frequency in the Danish Red and Danish Holstein (0.023 and 0.005). The dominance theory is supported by studies in humans, where it has been found that mutations associated with low GH release are often dominant (Missarelli et al, 1997;Gertner et al, 1998;Dannies, 2000). However, in the DJ breed the gene does not appear to be dominant and, therefore, an alternative explanation could be that the similar GH release in calves with different GH genotype is a result of a linked-gene effect in which the causing allele is not segregating in the tested calves.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is most likely due to random sampling, given the low expected values for the Val/Val genotype frequency in the Danish Red and Danish Holstein (0.023 and 0.005). The dominance theory is supported by studies in humans, where it has been found that mutations associated with low GH release are often dominant (Missarelli et al, 1997;Gertner et al, 1998;Dannies, 2000). However, in the DJ breed the gene does not appear to be dominant and, therefore, an alternative explanation could be that the similar GH release in calves with different GH genotype is a result of a linked-gene effect in which the causing allele is not segregating in the tested calves.…”
Section: Discussionmentioning
confidence: 99%
“…Patients III-1 and III-3 responded to GH treatment commencing at 9 years of age (mg kg À1 w À1 ) and 4 years of age (mg kg À1 w À1 ) respectively. This mutation, C>T c.626G>A p.R209H based on ENST00000323322, has been described previously as p.R183H in several pedigrees and shown to interfere with the secretion of GH (Deladoey, Stocker, & Mullis, 2001;Gertner, Wajnrajch, & Leibel, 1998;Marino et al, 2003;Miyata et al, 1997). The numbering in the previous publication was based on assigning the first amino acid of the GH protein following cleavage of the signal peptide.…”
Section: Identification Of Gh1 Mutationmentioning
confidence: 98%
“…In addition, three missense mutations have been described in IGHD type II patients, which lead to the exchanges of highly conserved amino acids and also suppress wtGH secretion to varying degrees (P89L, V110F, R183H; Duquesnov et al 1998, Gertner et al 1998, Binder et al 2001, Deladoey et al 2001. These three amino acids involved are located at protruding sites of the tertiary structure of the GH molecule and are possibly engaged in intramolecular interactions of the four a helices or in interactions with other GH molecules ( Fig.…”
Section: Introductionmentioning
confidence: 99%